Effect of method of cooking on identification of heat processed beef using polymerase chain reaction (PCR) technique - Arslan, Ali; İlhak, O. İrfan; Calicioglu, Mehmet (My University, 2006)
Effects of various cooking methods including boiling, roasting, pressure cooking, and pan frying on species determination of beef by PCR was studied. The meat was cooked by boiling at 97.5 C for 140, 200 or 230 min, by roasting at 200 C for 80, 120, or 150 min or by autoclaving at 120 C for 30, 60, or 90 min. The beef sample was pan fried until the meat was acceptable for sensory attributes (45 min, meat temperature 115 C, fat temp 173 C) and further cooked until unacceptable. DNA was extracted from samples taken after cooking and a 271 bp fragment of the mitochondrial DNA was amplified by PCR. The results indicated that with the exception of pan frying for 80 min, beef was determined in all meat samples including the broth and sauce of the roasted meat.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Meat Heat-treatment PCR Identification